Shaping the synaptic signal: molecular mobility inside and outside the cleft - Rusakov, Dmitri A. (Elsevier Applied Science Publishing, 2011)
Rapid communication in the brain relies on the release and diffusion of small transmitter molecules across the synaptic cleft. How these diffuse signals are transformed into cellular responses is determined by the scatter of target postsynaptic receptors, which in turn depends on receptor movement in cell membranes. Thus, by shaping information transfer in neural circuits, mechanisms that regulate molecular mobility affect nearly every aspect of brain function and dysfunction. Here we review two facets of molecular mobility that have traditionally been considered separately, namely extracellular and intra-membrane diffusion. By focusing on the interplay between these processes we illustrate the remarkable versatility of signal formation in synapses and highlight areas of emerging understanding in the molecular physiology and biophysics of synaptic transmission.